Introducing Excel spreadsheet calculations and numerical simulations with professional software into an undergraduate hydraulic engineering course - Bermúdez, María; Puertas, Jerónimo; Cea, Luis (Computer applications in engineering education, 2020)
This paper presents a comprehensive set of computer tools for implementing an active teaching–learning strategy on an undergraduate hydraulic engineering course, within the subject blocks of pressure flow and free surface flow. The tools comprise a number of simple Excel‐based applications, to enhance students’ understanding of basic concepts, plus a series of practical exercises using the free professional models EPANET and IBER, aimed at familiarizing students with the tools used in real practice. The application of the new methodology to a hydraulics course at the Civil Engineering School of the University of A Coruña (Spain) resulted in increased student satisfaction and engagement, as well as greater interaction with instructors and classmates. The applications and practical exercises are easily adaptable and freely available to the community to facilitate their application to other courses and/or degrees.